Nasal Associated Lymphoma Tumors - Reno Keumalazia Kamarlis; Vera Dewi Mulia; Benny Kurnia (Budapest International Research and Critics University, 2020)
This study analyses nasal associated lymphoma tumors, the results of histopathological examination obtained a picture that supports the establishment of a diffuse large B-cell lymphoma (DLBCL) with the characteristics of typical cells. This patient does not support an extranodal NK / T nasal lymphoma type cell because there are no glandular mucosa and clear cell peculiar changes as well as areas that experience necrosis, vascular destruction and fibrinoid deposits in blood vessel walls